2020
DOI: 10.1159/000512428
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Associated Health Risk Factors among Adults in Dubai, United Arab Emirates: Results from Dubai Household Survey 2019

Abstract: <b><i>Background:</i></b> The health and social burdens of diabetes mellitus (DM) are steadily increasing worldwide, reflecting the impact of urbanization, industrial transitions, and shifting to nonhealthy, sedentary life patterns’, as well as the high sugar, low-fiber food consumptions. All these factors have contributed to the global increase in the prevalence of DM and metabolic disorders. <b><i>Objectives:</i></b> The objective is to study the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…While there are studies that have established the prevalence of T2D in the Middle East and Africa, [21][22][23][24][25][26] there is limited information on the prevalence of eASCVD or on high/very high ASCVD risk in patients with T2D in this region. 3,[27][28][29][30][31] The CAPTURE study estimated the prevalence of ASCVD among patients with T2D across 13 countries from five continents and showed that one in three adults with T2D have established CVD, of which 9/10 had ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…While there are studies that have established the prevalence of T2D in the Middle East and Africa, [21][22][23][24][25][26] there is limited information on the prevalence of eASCVD or on high/very high ASCVD risk in patients with T2D in this region. 3,[27][28][29][30][31] The CAPTURE study estimated the prevalence of ASCVD among patients with T2D across 13 countries from five continents and showed that one in three adults with T2D have established CVD, of which 9/10 had ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Diabetes Federation (IDF) [ 58 ], the international prevalence of diabetes is 9.3%, whereas, in the United Arab Emirates (UAE), it reaches around 16.3% [ 59 ]. The prevalence of diabetes in the Northern Emirates of the UAE reached 25.1% among the UAE nationals and 19.1% among expatriates [ 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of diabetes in the Northern Emirates of the UAE reached 25.1% among the UAE nationals and 19.1% among expatriates [ 60 , 61 ]. Al Awadi et al [ 59 ] reported a higher prevalence of diabetes among Emiratis at 19.3% compared to 12.4% among expats. Recent studies in the UAE showed the prevalence of diabetes among Emirati adult females to be 8.6%, while the prevalence of prediabetes reached 24% [ 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 The high prevalence of traditional CVD risk factors, such as diabetes, hypertension (HTN) and obesity, among UAE nationals contributes significantly to this increased CVD risk. 2–4 Furthermore, chronic renal failure has also been shown to be an independent risk factor for CVD among UAE nationals. 5 …”
Section: Introductionmentioning
confidence: 99%
“…1 The high prevalence of traditional CVD risk factors, such as diabetes, hypertension (HTN) and obesity, among UAE nationals contributes significantly to this increased CVD risk. [2][3][4] Furthermore, chronic renal failure has also been shown to be an independent risk factor for CVD among UAE nationals. 5 The burden of CVD can be reduced by early risk assessment and stratification; therefore, primary prevention is a top priority for health policymakers.…”
Section: Introductionmentioning
confidence: 99%